Are eastern grey squirrels a big problem for bigleaf maple? - Bokor, Adrienn (University of Toronto, 2022)
Bigleaf maple (Acer macrophyllum Pursh) is an important tree species on the Pacific coast of North America. It is one of the few hardwoods in the Pacific Northwest and provides several ecological, economic, and social benefits. It supports a large variety of species, is used to make numerous items, and is culturally important to First Nations. However, for about the last ten years, bigleaf maple has been showing signs and symptoms of decline with an unknown cause in the Washington, Oregon, and California range of the species (Betzen, 2018; Christiansen, 2019). Given the important role bigleaf maple plays, its decline could have large-scale impacts. Root disease was suspected by forest professionals in Washington based on symptoms such as partial to entire crown dieback, reduced leaf size, and yellow flagging and dieback of entire branches. Forest professionals tested for and ruled out several potential biotic agents such as Verticillium albo-atrum, Verticillium dahlia, Armillaria, Ganoderma, and Xylella fastidiosa (Omdal & Ramsey-Kroll, 2012; Betzen, 2018). A newly published study in western Washington indicated that the cause of this decline is most likely linked to abiotic agents such as road proximity, increased land development, and escalating summer temperatures (Betzen et. al, 2021). Metro Vancouver Regional District in British Columbia, Canada, had a forest health report completed that identified bigleaf maple flagging in some parks. With little research regarding bigleaf maple decline and few reports on bigleaf maple in general in the British Columbia context, this present study investigates if there is a decline syndrome in Metro Vancouver Regional Parks and what the cause may be. Data were collected for GPS location, Dbh, and several crown health metrics such as dieback percent, canopy openness percent and chlorosis percent. Information was also gathered for the presence or absence of foliar diseases, fruiting bodies, damage, flagging and leaf tip dieback. General linear model regression (Morin et al, 2012) and direct ordination using correspondence analysis was performed using R to determine statistical significance of the data. This study found strong associations to bark-stripping indicating diminishing tree health. With eastern grey squirrels being an introduced species to the area, their known association to bark-stripping hardwoods, including maples (among other species), and their well-documented invasive behaviour of tree destruction in the United Kingdom, makes them the most likely culprit. Kretzschmaria deusta was also found to have strong associations to deteriorating tree health and with larger diameter trees. With strong associations of bark-stripping and Kretzschmaria deusta to declining tree health, this is a management concern for Metro Vancouver Regional District that needs to be addressed to prevent potentially large-scale impacts in the future. Recommendations include initiating management programs for eastern grey squirrels in highly effected parks such as Campbell Valley Regional Park and active monitoring for Kretzschmaria deusta along heavily used trails. It is also recommended to monitor for sooty bark disease (Cryptostroma corticale). Collaboration with the British Columbia Society for the Prevention of Cruelty to Animals (BC SPCA), invasives species councils, the regions’ municipalities and the province to create a unified and effective approach to eastern grey squirrel management in the Metro Vancouver Regional District and the rest of British Columbia is also suggested.